Assessing the Impact of Jakarta-Bandung High-Speed Rail Project toward Regional Socioeconomic Conditions: An Difference-in-Differences Analysis - Kusumawati, Balkis; Fauzi, Akhmad; Djuanda, Bambang; Barus, Baba (Jurnal Ekonomi Pembangunan, 2025)
This study evaluates the economic impact of the Jakarta–Bandung High-Speed Rail (JB-HSR) project, a key strategic initiative for promoting balanced and sustainable regional economic growth in Indonesia. We analyze four major regional indicators: Gross Regional Domestic Product (GRDP), investment, open unemployment, and poverty levels. Employing a Difference-in-Differences (DID) approach with panel data from 2013 to 2023, our findings reveal that the JB-HSR 's presence significantly increased GRDP and investment, and contributed to a decline in open unemployment within the directly affected regions. However, the project has not yet led to a statistically significant reduction in poverty, indicating uneven distribution of economic benefits across population segments. A spatial analysis further highlights substantial land-use changes around JB-HSR stations, reflecting the potential for future Transit-Oriented Development (TOD). These insights underscore the necessity for integrated spatial planning between central and regional governments, enhancement of local workforce capacities, and the implementation of inclusive investment and social policies to ensure the long-term sustainability and equitable distribution of JB-HSR project benefits.